OPTIMIZATION OF THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) BY SANGGING TO PREVENT CROSS INFECTION IN THE MATATAH CEREMONY - I Nyoman Gejir (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The Matatah is one of the religious ceremonies for Hindus in Bali. During the process of Matatah ceremony, the role of the Sangging (the ceremonial practicioner) is very important. The use of personal protective equipment (PPE) or Alat Pelindung Diri (APD) by the Sangging during the Matatah ceremony is crucial to prevent cross-infection. Several types of disease can be transmitted through the mouth, such Tuberculosis (TB), and Human Immunodeficiency Virus (HIV) / Acqired Immunodeficiency Syndrome (AIDS). The aim of this research is to provide information on optimizing the use of personal protective equipment (PPE) or Alat Pelindung Diri (APD) by the Sangging during the Matatah ceremony. This research is a literature review, addressing the issues with the relevant references, including: books, research findings, journals, and other scientific articles pertinent to the fields of health and religion. The results of this research shows that the Sangging’s knowledge about personal protective equipment (PPE) or Alat Pelindung Diri (APD) and cross infection prevention is very important, necessitating education for the Sangging by health care professional, as well as monitoring during the Matatah ceremony. Other efforts that can be made include creating guidelines for preventing cross-infection during the Matatah ceremony, involving experts in the field of health. The conclusion of this research is, that improving the behaviour of personal protective equipment (PPE) or Alat Pelindung Diri (APD) use by the Sangging during the Matatah ceremony can be achieved through continuous education and monitoring.